User's guide to plastic - Bruder, Ulf, 1946- (Hanser ; Hanser Publications, 2019)
Many technical books about plastics are too theoretical and difficult to read. The intention of this book is to offer something different: it is easy to read with examples taken from everyday life. It is suitable for readers at secondary school and university levels, and can be used for training activities in industry as well as for self-study.
Includes index.
Keywords: Plastics -- Handbooks, manuals, etc.; elektronické knihy; electronic books